Multicenter prospective observational study of dupilumab‐induced ocular events in atopic dermatitis patients. (16th February 2023) - Costedoat, Ingrid; Wallaert, Martin; Gaultier, Aurelie; Vasseur, Robin; Vanhaecke, Clelia; Viguier, Manuelle; Cordelette, Charles; Denoyer, Alexandre; Ferrier le Bouëdec, Marie‐Christine; Coutu, Adrien; Lamiaux, Marie; Tran, Thi Ha Châu; et al.
Abstract: Background: Although ocular adverse events are frequent in AD patients treated with dupilumab, their characterization remains limited due to a lack of prospective studies with a systematic ophthalmological examination. Objective: To examine the incidence, characteristics and risk factors of dupilumab‐induced ocular adverse events. Methods: A prospective, multicenter, and real‐life study in adult AD patients treated with dupilumab. Results: At baseline, 27 out of 181 patients (14.9%) had conjunctivitis. At week 16 (W16), 25 out of 27 had improved their conjunctivitis and 2 remained stable and 34 out of 181 patients (18.7%) had dupilumab‐induced blepharoconjunctivitis: either de novo ( n  = 32) or worsening of underlying blepharoconjunctivitis ( n  = 2). Most events (27/34; 79.4%) were moderate. A multivariate analysis showed that head and neck AD (OR = 7.254; 95%CI [1.938–30.07]; p  = 0.004), erythroderma (OR = 5.635; 95%CI [1.635–21.50]; p  = 0.007) and the presence of dry eye syndrome at baseline (OR = 3.51; 95%CI [3.158–13.90]; p  = 0.031) were independent factors associated with dupilumab‐induced blepharoconjunctivitis. Limitations: Our follow‐up period was 16 weeks and some late‐onset time effects may still occur. Conclusion: This study showed that most dupilumab‐induced blepharoconjunctivitis cases are de novo. AD severity and conjunctivitis at baseline were not found to be associated risk factors in this study.